2021
DOI: 10.1016/j.arthro.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Iliopsoas Tenotomy for Pain After Total Hip: A Great Operation IF the Diagnosis Is Right

Abstract: Iliopsoas tendon pain can be a frustrating condition for both patients and surgeons after total hip arthroplasty. It is difficult to diagnose definitively, as there is no imaging modality that offers reliable information and there are numerous causes of persistent groin pain in this patient population. The pain can ruin the results of an otherwise wellfunctioning total hip arthroplasty. Patients who respond best to arthroscopic iliopsoas tenotomy are those with isolated pain with hip flexion activities and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…With the mature development of hip arthroscopy technology, arthroscopy has been well used in the treatment of femoroacetabular impingement, ischiofemoral impingement, and gluteus medius tendon injury. Blackman 10 suggested that once isolated pain in the hip originates from iliopsoas tendon tightness, arthroscopic severance of the tendon is a very safe and effective treatment modality. The theory provides a theoretical basis for the choice of tendon dissection in this operation.…”
Section: Discussionmentioning
confidence: 99%
“…With the mature development of hip arthroscopy technology, arthroscopy has been well used in the treatment of femoroacetabular impingement, ischiofemoral impingement, and gluteus medius tendon injury. Blackman 10 suggested that once isolated pain in the hip originates from iliopsoas tendon tightness, arthroscopic severance of the tendon is a very safe and effective treatment modality. The theory provides a theoretical basis for the choice of tendon dissection in this operation.…”
Section: Discussionmentioning
confidence: 99%
“…As with any surgery, a mutual decision between the surgeon and the patient is determined based on indications, 6 potential risks, and benefits of the procedure. In terms of indications, acetabular component revision is often reserved for patients with significant implant malposition (≥8 mm acetabular prominence).…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 Additionally, lumbar spine, intra-abdominal, retro-peritoneal and vascular pathologies should be evaluated. 6 , 7 Screening for these entities is outside the scope of this technique article.…”
Section: Introductionmentioning
confidence: 99%